Factors affecting Osseointegration: A Literature Review - Goutam, Manish; Chandu, GS; Mishra, Sunil Kumar; Singh, Madhvi; Tomar, Brajendra Singh (Journal of Orofacial Research, 2013)
The purpose of this literature review is to collect the published data concerning factors affecting osseointegration. Popularity and large demand of dental implant makes this study essential because success of dental implant is directly related to the principle of osseointegration, a process of implant-bone interaction that finally leads to bone-implant anchorage. To identify relevant literature an electronic search was performed using term osseointegration and dental implant on PubMed central. Titles and abstracts were screened and articles that fulfilled the inclusion criteria were selected for full text reading. Review of selected articles enabled us to enlist various factors which have significant effects on osseointegration either by enhancing or inhibiting it. Based on the review literature, it is concluded that there are factors which when considered may increase osseointegration which in turn will increase success of dental implant and some factors play an inhibiting role for bone-implant contact.